Natchez burning - Iles, Greg (New York William Morrow, 2014)
Growing up in Natchez, Mississippi, Penn Cage learned everything he knows about honor and duty from his father, Tom Cage. But now the beloved family doctor and pillar of the community is accused of murdering Violet Turner, the nurse with whom he worked in the dark days of the early 1960s. Penn is determined to save his father, even though Tom, evoking doctor-patient privilege, refuses to speak up in his own defense.
Keywords: Cage, Penn (Fictitious character) -- Fiction; Trials (Murder) -- Fiction; Natchez (Miss.) -- Fiction